Hubungan komunitas zooplankton dengan faktor oseanografi di ekosistem terumbu karang Manokwari - S. Tururaja, Tresia; Bawole, Roni; Mogea, Rina; Murtihapsari (Cassowary, 2025)
Zooplankton play an important dual role in marine ecosystems as food webs connectors and sensitive indicators of water quality. This study examines the composition, abundance, and relationship of zooplankton communities with oceanographic parameters in the coral reef ecosystem of Manokwari Waters. Samples were collected from three observation stations: Kaki Island, Lemon Island, and Marampa Port, using a 25 μm plankton net. Morphological identification resulted in six classes of zooplankton, namely Hexanauplia, Gastropoda, Bivalve, Malacostraca, Branchiopoda, and Ostracoda, for a total of 23 species. The class Hexanauplia dominates in all locations, with the most abundant species being Undinula vulgaris (10 individuals), Calanus sinicus (7), and Eurytemora pacifica (6). Cluster analysis based on the Bray-Curtis similarity index with the Average Linkage method shows the similarity of zooplankton communities between Marampa Port and Lemon Island. Kaki Island forms a separate cluster, indicating differences in species composition spatially. The highest abundance was recorded in the Hexanauplia class with an abundance index of >2,500 cells/L in some species. Canonical Correspondence Analysis (CCA) revealed a positive correlation between DO and Bivalvia (+0.99), temperature with Gastropoda (+0.92), and salinity with Hexanauplia (+0.28). Environmental factors such as temperature, DO, pH, and depth have been shown to influence the spatial distribution and diversity of communities. These findings reinforce the dual role of zooplankton as a fundamental food source for benthic organisms such as the soft coral Sarcophyton sp. and as an effective bioindicator for monitoring the health of tropical coastal ecosystems. Keywords: zooplankton, Undinula vulgaris, Hexanauplia, oceanographic parameters, Manokwari